Gambaran Karakteristik Sosiodemografi Penderita Kusta di Kabupaten Aceh Utara Tahun 2017-2021 - Salsabila, Islah; Khairunnisa, Cut; Mellaratna, Wizar Putri (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Introduction: Leprosy is an infectious disease which is still a health problem in Indonesia. Indonesia is ranked third as the country with the most leprosy patients in the world after India and Brazil. In 2021, it was reported that there were 10.976 new cases of leprosy in Indonesia and the prevalence of leprosy in Aceh in 2021 was found to be 321 cases of leprosy. Research objective: to describe the sociodemographic characteristics (age, sex, type of leprosy and level of disability) of leprosy patients in North Aceh District in 2017-2021. Method: descriptive study with a cross-sectional approach to leprosy patients in North Aceh District. Samples were taken by using total sampling technique. Results and Discussion: In this study, it was found that the distribution of leprosy patients based on age was mostly found in the adult age categories, which is 26-45 years with 76 people (44.4%), as many as 100 people with leprosy (58.5%) were men, people with the Multibacillary type was found in 119 people (69.6%) and there were 157 patients with grade 0 disabilities (91.8%). Conclusion: The distribution of leprosy based on age was mostly found in the adult age category (26-45 years), the majority of leprosy patients were male, the most common type of leprosy was Multibacillary leprosy and the majority of leprosy patients have grade 0 defects.  Keywords: Leprosy, Characteristic, Sociodemography  ABSTRAK Pendahuluan: Kusta merupakan salah satu penyakit menular yang masih menjadi masalah kesehatan di Indonesia. Indonesia menempati peringkat ketiga negara dengan penderita kusta terbanyak di dunia setelah India dan Brazil.  Tahun 2021, dilaporkan terdapat sebanyak 10.976 kasus baru kusta di Indonesia dan prevalensi penyakit kusta di Aceh pada tahun 2021 ditemukan sebanyak 321 kasus kusta. Tujuan penelitian: untuk mengetahui gambaran karakteristik sosiodemografi (usia, jenis kelamin, tipe kusta dan tingkat cacat kusta) penderita kusta di Kabupaten Aceh Utara tahun 2017-2021. Metode: penelitian deskriptif dengan pendekatan cross-sectional terhadap penderita kusta di Kabupaten Aceh Utara. Sampel diambil dengan teknik pengambilan sampel total sampling. Hasil dan pembahasan: penelitian ini didapatkan bahwa distribusi penderita kusta berdasarkan usia sebagian besar ditemukan pada kategori usia dewasa, yaitu 26-45 tahun sebanyak 76 orang (44,4%), sebanyak 100 orang penderita kusta (58,5%) adalah laki-laki, penderita penyakit kusta dengan tipe Multibasiler ditemukan sebanyak 119 orang (69,6%) dan terdapat 157 penderita mengalami cacat tingkat 0 (91,8%). Kesimpulan: Distribusi penderita kusta berdasarkan usia paling banyak ditemukan pada kategori usia dewasa (26-45 tahun), mayoritas penderita kusta berjenis kelamin laki-laki, paling banyak ditemukan penderita kusta dengan tipe kusta Multibasiler dan mayoritas penderita kusta mengalami cacat tingkat 0. Kata Kunci : Kusta, Karakteristik, Sosiodemografi